Update of literature from cystic fibrosis registries 2012–2015. Part 6: Epidemiology, nutrition and complications. Issue 3 (29th September 2016) - Salvatore, Donatello; Buzzetti, Roberto; Mastella, Gianni
Summary: Patient registries provide useful information to afford more knowledge on rare diseases like Cystic Fibrosis (CF). Twenty‐two studies originating from national CF registries, focusing on demographics, survival, genetics, nutritional status, and non‐pulmonary complications, were published between December 2011 and March 2015. The purpose of this review article is to examine these reports, aiming attention to the clinical characteristics of CF patients included in the registries, current, and estimated future epidemiological data, the role of gender gap, the increasing survival in different countries. Some studies offer insights into pubertal growth and non‐pulmonary complications, such as liver disease, nephropathy, and cancer.Pediatr Pulmonol. 2017;52:390–398. © 2016 Wiley Periodicals, Inc.